Impact of selected factors on the perception of the macroeconomic and financial environment of SMES (empirical study from Czech republic and Slovak republic) - Dobeš, Kamil; Virglerová, Zuzana; Kramoliš, Jan (Univerzita Pardubice, 2019)
The business environment is the one of the most important cause of successful business. The important role plays macroeconomic and financial environment and entrepreneur’s perceptions of them. The aim of the article is to evaluate and compare the perception of business environment and its impact on entrepreneurship in the Czech Republic and in the Slovak Republic. The article deals with the results of the empirical questionnaire survey, which was completed in 2018 in the Czech Republic. The research works with 641 valid answers. Research focused on small and medium-sized enterprises, as they are a major catalyst for the economic growth of individual economies. Two main research questions were set to compare the perception of macroeconomic environment and financial environment and its impact on business in selected countries. Another 4 research questions were formulated in relation to compare two main research questions in relation to selected factors (length of the business and entrepreneur’s education). In process of solving the formulated research questions tables, descriptive characteristics and Person coefficient of contingency were used. Despite the fact that the macroeconomic environment in the Czech Republic and Slovakia is comparable, perceptions of the business environment differ in several aspects.
Keywords: business environment; SMEs; perception; bank’s interest rates; Czech republic; Slovak republic; B22; G21; L26